2004
DOI: 10.1164/rccm.200310-1348oc
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study of Fel d1 and Der p1 Exposure in Infancy and Childhood Wheezing

Abstract: The impact of domestic exposure to cat allergen (Fel d1) and house dust mite (Der p1) on wheezing from birth to the age of 4 years was investigated in a multicenter prospective birth cohort; 1,611 mothers were recruited before delivery in Ashford, England, and Barcelona and Menorca, Spain. Exposures were gathered via dust sample collection at children's home in their first year of life. Families provided complete outcome data (wheezing status in all 4 years) for 1,289 children. Domestic allergen levels varied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
79
3
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(93 citation statements)
references
References 33 publications
10
79
3
1
Order By: Relevance
“…For children with an atopic mother, these results are in accordance with those of other studies that do show an increased risk of wheeze in children with an asthmatic mother. 11,13 With respect to our results in children with a nonatopic mother, Polk et al 11 observed no effects of cat allergen exposure on the risk of wheeze for children with a nonasthmatic mother, whereas Celedon et al 13 observed protective effects of cat allergen exposure. However, the latter study included only children with at least one parent with a history of asthma, which makes it difficult to compare their results with ours.…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations
“…For children with an atopic mother, these results are in accordance with those of other studies that do show an increased risk of wheeze in children with an asthmatic mother. 11,13 With respect to our results in children with a nonatopic mother, Polk et al 11 observed no effects of cat allergen exposure on the risk of wheeze for children with a nonasthmatic mother, whereas Celedon et al 13 observed protective effects of cat allergen exposure. However, the latter study included only children with at least one parent with a history of asthma, which makes it difficult to compare their results with ours.…”
Section: Discussionsupporting
confidence: 52%
“…This is in accordance with the results of others. 5,8,11 We did observe an association between cat allergen exposure and persistent wheeze, which was borderline significant for the total study population and showed similar trends for children with and without an atopic mother. For children with an atopic mother, these results are in accordance with those of other studies that do show an increased risk of wheeze in children with an asthmatic mother.…”
Section: Discussionmentioning
confidence: 47%
See 2 more Smart Citations
“…krakow inner city area study allergens. Allergic sensitisation to dog or cat allergens is believed to be an important risk factor for asthma and asthma symptoms, [1][2][3][4][5][6][7][8][9][10][11][12] and many studies reported positive correlations between the ownerships of pets and the excess in the occurrence of asthma symptoms, asthma diagnosis or asthma medication treatment. It was also shown that asthmatics are more likely than nonasthmatics sensitised to pet allergens and exposures to Can f 1 and Fel d 1 as low as 2 mg/g of house dust and 1 mg/g of dust, respectively, have been assumed as clinically relevant risk thresholds [13][14][15].…”
Section: Introductionmentioning
confidence: 99%